2011
DOI: 10.1074/jbc.m110.211912
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Specificity Overlap and Interaction between Adrenoleukodystrophy Protein (ALDP/ABCD1) and Adrenoleukodystrophy-related Protein (ALDRP/ABCD2)

Abstract: X-linked adrenoleukodystrophy (X-ALD) is a neurodegenerative disorder caused by mutations in the ABCD1 gene, which encodes a peroxisomal member of the ATP-binding cassette (ABC) transporter subfamily D called ALDP. ALDP is supposed to function as a homodimer allowing the entry of CoA-esters of very-long chain fatty acids (VLCFA) into the peroxisome, the unique site of their ␤-oxidation. ALDP deficiency can be corrected by overexpression of ALDRP, its closest homolog. However, the exact nature of the substrates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 37 publications
(42 reference statements)
5
40
0
2
Order By: Relevance
“…The level of C24:6 was decreased only in the presence of ABCD2 and ABCD2-ABCD2, ABCD1-ABCD2, or ABCD2-ABCD1 chimeric proteins but not in the presence of ABCD1 or ABCD1-ABCD1 chimeric dimers. This result reinforces the supposed important role of ABCD2 in PUFA metabolism (8,10,49) and is in agreement with the fact that ABCD2 expression is regulated by PUFA (50). It also surprisingly shows that one TMD from ABCD2 is sufficient to ensure C24:6-CoA transport.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The level of C24:6 was decreased only in the presence of ABCD2 and ABCD2-ABCD2, ABCD1-ABCD2, or ABCD2-ABCD1 chimeric proteins but not in the presence of ABCD1 or ABCD1-ABCD1 chimeric dimers. This result reinforces the supposed important role of ABCD2 in PUFA metabolism (8,10,49) and is in agreement with the fact that ABCD2 expression is regulated by PUFA (50). It also surprisingly shows that one TMD from ABCD2 is sufficient to ensure C24:6-CoA transport.…”
Section: Discussionsupporting
confidence: 76%
“…From the increased ␤-oxidation of C24:6, we could have expected an increase of DHA. However, we previously demonstrated that ABCD2 expression increased ␤-oxidation of DHA (10). It is therefore consistent to find that expression of ABCD2 or of chimeric proteins containing at least one ABCD2 moiety result in equilibrium.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…En effet, à la suite d'étapes d'élon-gation et de désaturation de l'acide α-linolénique (C18:3 n-3) dans le réticulum endoplasmique, il y a formation de C24:6 n-3 qui subit ensuite un cycle de β-oxydation (perte de 2 atomes de carbone) dans le peroxysome pour former le DHA. ABCD2 pourrait ainsi participer à la fois au transport du DHA pour sa dégradation et au transport de son précurseur immédiat pour sa synthèse [12][13][14]. Concernant ABCD3, là encore, il apparaît que la surexpression d'ABCD3 peut compenser biochimiquement la déficience en ABCD1, signe qu'ABCD3 peut transporter des AGTLC saturés et monoinsaturés, mais avec une moins bonne efficacité [9].…”
Section: Les Transporteurs Abc De La Membrane Peroxysomaleunclassified
“…Chez les mammifères, plusieurs études ont suggéré qu'ABCD1, ABCD2 et ABCD3 sont fonctionnels sous forme d'homodimères. En fait, diffé-rentes équipes, dont la nôtre, ont démontré l'existence d'interactions physiques entre les différents hémitrans-porteurs, indiquant qu'homodimères et hétérodimères coexistent [14,16]. Les niveaux d'expression relatifs de ces trois transporteurs varient fortement, que ce soit au cours du développement ou en fonction des tissus [17,18].…”
Section: Les Transporteurs Abc De La Membrane Peroxysomaleunclassified